Multicountry study of SARS-CoV-2 and associated risk factors among healthcare workers in Côte d'Ivoire, Burkina Faso and South Africa. (24th September 2022) - Kribi, Sarah; Touré, Fidèle; Mendes, Adriano; Sanou, Soufiane; Some, Arsène; Aminou, Abdoul M; Belarbi, Essia; Griessel, Rosemary; Hema, Arsène; Kabore, Firmin; Pitzinger, Paul; Strydom, Amy; et al.
Abstract: Background: Reports on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread across Africa have varied, including among healthcare workers (HCWs). This study assessed the comparative SARS-CoV-2 burden and associated risk factors among HCWs in three African countries. Methods: A multicentre study was conducted at regional healthcare facilities in Côte d'Ivoire (CIV), Burkina Faso (BF) and South Africa (SA) from February to May 2021. HCWs provided blood samples for SARS-CoV-2 serology and nasopharyngeal/oropharyngeal swabs for testing of acute infection by polymerase chain reaction and completed a questionnaire. Factors associated with seropositivity were assessed with logistic regression. Results: Among 719 HCWs, SARS-CoV-2 seroprevalence was 34.6% (95% confidence interval 31.2 to 38.2), ranging from 19.2% in CIV to 45.7% in BF. A total of 20 of 523 (3.8%) were positive for acute SARS-CoV-2 infection. Female HCWs had higher odds of SARS-CoV-2 seropositivity compared with males, and nursing staff, allied health professionals, non-caregiver personnel and administration had higher odds compared with physicians. HCWs also reported infection prevention and control (IPC) gaps, including 38.7% and 29% having access to respirators and IPC training, respectively, in the last year. Conclusions: This study was a unique comparative HCW SARS-CoV-2 investigation in Africa. Seroprevalence estimates varied, highlighting distinctive population/facility-level factors affecting COVID-19 burden and the importance of established IPC programmes to protect HCWs and patients.